The seven sins of L2 research: A review of 30 journals' statistical quality and their CiteScore, SJR, SNIP, JCR Impact Factors. (November 2019) - Al-Hoorie, Ali H.; Vitta, Joseph P.
This report presents a review of the statistical practices of 30 journals representative of the second language field. A review of 150 articles showed a number of prevalent statistical violations including incomplete reporting of reliability, validity, non-significant results, effect sizes, and assumption checks as well as making inferences from descriptive statistics and failing to correct for multiple comparisons. Scopus citation analysis metrics and whether a journal is SSCI-indexed were predictors of journal statistical quality. No clear evidence was obtained to favor the newly introduced CiteScore over SNIP or SJR. Implications of the results are discussed.